Virus de la inmunodeficiencia humana y desnutrición grave en paciente masculino de 41 años de edad - Mejia Fuentes, Denisse Pamela (2018)
Acquired immunodeficiency virus is an infectious disease caused by a transmissible agent. In the absence of effective treatment, the virus produces a state of progressive immunodeficiency that is mainly due to a decrease in CD4 T lymphocytes. The most frequent routes of transmission through which the infection has occurred have been blood (blood transfusion and blood products, sharing contaminated syringes for the injection of drugs) and sexual (in both male and female relationships, as well as male- man). Confidential testing means that the results of the test include your name and other identifying information, but only those authorized to see your medical record will see those results. Positive results of the virus screening test will be reported to local or state health departments for inclusion in statistical reports. The treatment consists in the administration of three medicines for the virus (called antiretroviral drugs). Current antiretroviral therapy is highly effective, well tolerated and easy to administer (treatment can be done by taking a single pill once a day). The medicines prevent the virus from reproducing (replicating), which reduces the concentration in the body. By having less concentration of the virus in the body the immune system has more chance of recovering. Even if there is still some virus in the body, the immune system is strong enough to fight infections and certain types of cancer related to the virus